Use of Management Accounting and Social Performance: - Ginette, IPOUMB Polienne (STIE Malangkucecwara, 2025)
This paper examines the influence of management accounting on social performance. Quantitative research was conducted. Primary data obtained through the administration of questionnaires to 199 Cameroonian multi-sector small and medium enterprises (SMEs) in 5 regions of Cameroon was used. While regression analysis with the aid of STATA 20 software was utilized in testing the hypothesis. The empirical findings show that there exists a significant and positive association between the use of management accounting and social performance. The analysis reveals that SMEs that use cost, budget, scoreboard and profitability ratio data in particular have improved social performance. These findings extend the literature on the importance of management accounting. It helps managers have a better understanding of the benefits to implement management accounting practice. Moreover, the research results will be useful for managers to encourage SMEs in Cameroon to implement management accounting practices to enhance not only financial but also social performance.